Main differentiating issues in aligning information systems with business performance - Fernandes, Silvia Brito (2013)
The information systems and technologies (IS/IT) are a decisive platform in the response capacity of organizations to the new management imperatives through new solutions that permit to improve their competitive position. As information management is a highly differentiating area, the present study compares several enterprises of different sectors, located (headoffice or branch) in the Algarve region, with the aim of systematising the main differentiating issues related with adoption, restructuring and implementation of information systems and supportive technologies. Every organization should define an accurate and in time plan which, in case of adopting and implementing information systems, has to analyse results within the same plan and on a yearly basis of the system's activity always aligned with the business strategy. Given the potential of ERP and CRM as powerful tools to guide customer-oriented understanding, greater attention is required on their economic viability for sustainable business dynamics.